Two freedoms. (Poetic) fragments of Michel Houellebecq - Wójcik, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
This article discusses the poetry of Michel Houellebecq. Its reading as a world-view statement is defined by its key notion of freedom. The thus specified reading enables one to identify various meanings of the notion included in the poems of the French writer: the philosophical and the social meanings.